Answer: ![y = 2x -6](https://tex.z-dn.net/?f=y%20%3D%202x%20-6)
Step-by-step explanation:
Since, If (x,y) represents the coordinates of a line, then after dilation about the origin by the scale factor k, the coordinates of the resultant line will get by the rule,
![(x,y)\rightarrow (kx,ky)](https://tex.z-dn.net/?f=%28x%2Cy%29%5Crightarrow%20%28kx%2Cky%29)
Here, The equation of the given line is,
y = 2x - 4
x-intercept and y-intercept of the line are (2,0) and (0,-4) respectively,
Hence, the line y = 2x - 4 will be passes through the points (2,0) and (0,-4),
By the above property,
The dilated line about the origin will be passes through the points (3,0) and (0,-6), ( Because (3/2× 2, 3/2×0) = (3,0) and (3/2×0, 3/2×-4) = (0,-6) )
Hence, the equation of transformed line after dilation,
![y-0=2(x-3)](https://tex.z-dn.net/?f=y-0%3D2%28x-3%29)
![y-0=2x-6](https://tex.z-dn.net/?f=y-0%3D2x-6)
![y=2x-6](https://tex.z-dn.net/?f=y%3D2x-6)